2022
DOI: 10.1177/20416695221128844
|View full text |Cite
|
Sign up to set email alerts
|

Individual fixation tendencies in person viewing generalize from images to videos

Abstract: Fixation behavior toward persons in static scenes varies considerably between individuals. However, it is unclear whether these differences generalize to dynamic stimuli. Here, we examined individual differences in the distribution of gaze across seven person features (i.e. body and face parts) in static and dynamic scenes. Forty-four participants freely viewed 700 complex static scenes followed by eight director-cut videos (28,925 frames). We determined the presence of person features using hand-delineated pi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Even though most humans tend to fixate close to the eye region within a face ( Birmingham, Bischof, & Kingstone, 2008 ; Foulsham, Cheng, Tracy, Henrich, & Kingstone, 2010 ; Klin, Jones, Schultz, Volkmar, & Cohen, 2002 ; Peterson & Eckstein, 2012 ), significant individual differences exist. Preferred fixation landing positions can be as low as the mouth and prove consistent for complex static scenes ( Broda & de Haas, 2022b ), portraits ( Peterson & Eckstein, 2013 ), director-cut videos ( Broda & de Haas, 2022a ), and natural free-viewing situations ( Peterson, Lin, Zaun, & Kanwisher, 2016 ). Future studies should test whether interindividual variability in the saccadic reaction time advantage afforded by faces and eyes is linked to individual differences in face and eye salience.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Even though most humans tend to fixate close to the eye region within a face ( Birmingham, Bischof, & Kingstone, 2008 ; Foulsham, Cheng, Tracy, Henrich, & Kingstone, 2010 ; Klin, Jones, Schultz, Volkmar, & Cohen, 2002 ; Peterson & Eckstein, 2012 ), significant individual differences exist. Preferred fixation landing positions can be as low as the mouth and prove consistent for complex static scenes ( Broda & de Haas, 2022b ), portraits ( Peterson & Eckstein, 2013 ), director-cut videos ( Broda & de Haas, 2022a ), and natural free-viewing situations ( Peterson, Lin, Zaun, & Kanwisher, 2016 ). Future studies should test whether interindividual variability in the saccadic reaction time advantage afforded by faces and eyes is linked to individual differences in face and eye salience.…”
Section: Discussionmentioning
confidence: 71%
“…Finally, it is unclear to which extent rapid saccades in the saccadic choice paradigm rely on general mechanisms of gaze control. Recently, we found that the individual tendency to fixate faces in scenes is strongly correlated to the tendency to fixate eyes within faces ( Broda & de Haas, 2022a ; Broda & de Haas, 2022b ). Even though most humans tend to fixate close to the eye region within a face ( Birmingham, Bischof, & Kingstone, 2008 ; Foulsham, Cheng, Tracy, Henrich, & Kingstone, 2010 ; Klin, Jones, Schultz, Volkmar, & Cohen, 2002 ; Peterson & Eckstein, 2012 ), significant individual differences exist.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, observers are more likely to look at the eye region when the depicted person looks at the camera while talking increases the number of mouth fixations ( Vo et al, 2012 ). At the same time, a recent study found that individual biases in person viewing generalize from static to dynamic scene viewing ( Broda & de Haas, 2022 ) and individual fixation behavior toward static faces is highly predictive of gaze behavior during real world interactions ( Peterson et al, 2016 ). Additionally, even screen-based gaze behavior that does not generalize to real-world interactions may have diagnostic value in clinical contexts ( Adolph & West, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on the eye and mouth regions (e.g., Kim et al, 2022), even though average and expert face observers tend to look somewhere in between (Linka et al, 2022;Peterson & Eckstein, 2012). In fact, we ourselves plead guilty to this oversight (Broda & de Haas, 2022a, 2022bde Haas et al, 2016de Haas et al, , 2021de Haas & Schwarzkopf, 2018). But there is more to faces.…”
mentioning
confidence: 99%